Maternal mitochondrial inheritance in two Fusarium pathogens of prickly ash (Zanthoxylum bungeanum) in northern China. (4th March 2019) - Zhou, Xue; Cao, Zhi-Min; Liu, Xin; Kim, Hye-Seon; Proctor, Robert H.; O'Donnell, Kerry
ABSTRACT: Mitochondrial inheritance in Fusarium zanthoxyli and F. continuum, two canker-inducing pathogens of prickly ash ( Zanthoxylum bungeanum ) in northern China, was investigated by genotyping ascospore progeny obtained from laboratory crosses. Polymorphic regions of the mitochondrial genomes (mitogenomes) that contained indels and single-nucleotide polymorphisms (SNPs) were identified via comparative analyses of the complete mitogenomes of the parents used in the intraspecific crosses. A reciprocal genetic cross of F. zanthoxyli NRRL 66714 × NRRL 66285, and a separate cross of F. continuum ♀ NRRL 66286 × ♂ NRRL 66218, revealed that mitochondria were only inherited from the maternal parent. In addition, the reciprocal cross demonstrated that mitochondrial inheritance is not linked to mating type. Gene order in the circular mitogenomes of the prickly ash pathogens was identical to that previously reported for other fusaria and members of the Hypocreales, except that the TRNL tRNAs were duplicated in F. zanthoxyli NRRL 66714. The genomes contained 14 polypeptide-encoding genes involved in oxidative respiration, one intron-encoded ribosomal protein ( rps3 ) gene, two ribosomal RNA (rRNA) genes, and 26–28 tRNA genes. The F. zanthoxyli mitogenomes were 80.9 and 98.7 kb in length, whereas those of F. continuum were considerably shorter and nearly identical in length at 63.4 kb. The significant differences in mitogenome length were primarily due to variable numbers of introns and open reading frames (ORFs) encoding hypothetical proteins.